Influence of prosthetic joint line position on outcome after total knee replacement - Choudhary, Preetesh; Bahre, Skand (International Journal of Research in Orthopaedics, 2017)
Background: The current study had been designed so as to assess whether joint line elevation and change in patellar tendon length influences knee flexion after primary cruciate retaining TKR. Methods: This prospective study involved patients with advanced degenerative joint disease involving one or both knees who presented to the outpatient department of a tertiary care hospital. Exclusion criteria were any prior knee surgery. Surgery was performed under tourniquet with standard medial para-patellar arthrotomy to expose all our knees. In the study radiological assessment was done by true lateral X-ray view of knee in 30 degree of flexion. We choose Caton-Deschamps indices (CI) for diagnosis of post TKR patella infera and joint line elevation. CI<0.6 was defined as patella infera (normal range of CI 0.60-1.45). After all data collection comparison was done between joint line elevation versus without joint line elevation patients (with/without patellar tendon shortening) range of movement. Results: Total of 100 patients (72 females and 28 males) with 176 knees (bilateral=76, unilateral=24) who fulfilled the above said criteria involved in study. The mean age of the patients at the time of surgery was 64.4 years with range of 54 years to 80 years. The average follow up of 24 months, with minimum follow up of 18 months. Average range of motion (ROM) in NO Joint line elevation/patella tendon shortening patient measured 107.2°, and joint line elevation with patellar tendon shortening (prior patella infera) and joint line elevation without patella tendon shortening(prior patella infera) patient average ROM was measured 86.7 and 87.8 degree respectively. Conclusions: In our study patellar tendon shortening and joint line elevation reduces ROM knee. Mechanical factors also explain the association between joint line elevation and patellar tendon length with range of motion. Reduction in length of extensor apparatus reduces the range of flexion.